An exploration of grade 2 learners’ experiences in solving addition and subtraction word problems - Cheva, G; Makamure, Chipo; Jojo, ZMM (SAINTIS Publishing, 2023)
Mathematics has always been a major part of school curricula in most countries. It provides a variety of useful tools that help students to solve problems that they encounter in everyday life. Mathematical tools are considered powerful, as long as one knows how to employ them across a range of suitable situations. However, selecting and using these tools appropriately appear to be challenging for many students. Because of this, word problems have been included in mathematics education to offer practice for students in applying mathematical skills effectively in various problem situations confronted in everyday circumstances. In addition, there is limited research about how learners in the foundation phase (Grades 1-3) solve addition and subtraction word problems. A relatively recent review of South African studies on mathematics education has revealed a paucity of research at the primary school level. This study therefore seeks to explore grade 2 learners’ experiences in solving addition and subtraction word problems. A qualitative research was conducted to describe grade 2 learners experience whilst solving addition and subtraction problems. Only 6 learners in grade 2 were selected to participate in this study. Learners demonstrated a strong preference for paper and pencil methods as well as the standard algorithm, when solving problems in word format. However, little evidence exists within the study that any of the learners conceptually understood the algorithm. The use of base 10 blocks to model the partial sums and partial differences algorithms would help most of the learners to develop a conceptual understanding of addition and subtraction of word problems in mathematics.